Effect of signaling reinforcement on resistance to change in a multiple schedule - Bell, Matthew C.; Seip, Katharine M.; Fitzsimmons, Kathleen S. (Behavioural processes, 2007)
This study evaluated the effect of a signal on resistance to change using a multiple schedule of reinforcement. Experiment 1 presented pigeons with three schedules: a signaled delay to reinforcement schedule (a two-link chain schedule with a variable-interval 120-s initial link followed by a 5-s fixed-time schedule), an unsignaled delay schedule (a comparable two-link tandem schedule), and an immediate, zero-delay variable-interval 125-s schedule. Two separate disruption procedures assessed resistance to change: extinction and adding a variable-time 20-s schedule of reinforcement to the inter-component interval. Resistance to change tests were conducted twice, once with the signal stimulus (the terminal link of the chain schedule) present and once with it absent. Results from both disruption procedures showed that signal absence reduced resistance to change for the pre-signal stimulus. In probe choice tests subjects strongly preferred the signal stimulus over the unsignaled stimulus and exhibited no reliable preference when given a choice between the signal stimulus and immediate stimulus. Experiment 2 presented two equal signaled schedules where, during resistance to change tests, the signal remained for one schedule and was removed for the second. Resistance to change was consistently lower when the signal was absent.